2017
DOI: 10.15261/serdj.24.97
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Separation of Pt and Pd by an Imidazolium-Based Ionic Liquid Combined with Phosphonium Chloride

Abstract: Extraction and separation of Pt(IV) and Pd(II) from a hydrochloric acid solution was examined with a mixture of undiluted ionic liquids, 1-methyl-3-octylimidazolium bis(trifluoromethylsulfonyl)imide ([C 8 mim][Tf 2 N]) and trihexyltetradecylphosphonium chloride ([P 6,6,6,14 [Tf 2 N] shows a high selectivity for Pt(VI), whereas [P 6,6,6,14 ][Cl] has a high extraction ability for both Pt(IV) and Pd(II). The addition of [P 6,6,6,14 ][Cl] to [C 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…If a PGM other than Pd could be selectively extracted from a mixture of PGMs, the extraction process could be considerably simplied. However, such examples are quite rare in the literature, [18][19][20] because the ligand exchange and chloro complex formation of Pd is the fastest among the PGMs.…”
Section: Introductionmentioning
confidence: 99%
“…If a PGM other than Pd could be selectively extracted from a mixture of PGMs, the extraction process could be considerably simplied. However, such examples are quite rare in the literature, [18][19][20] because the ligand exchange and chloro complex formation of Pd is the fastest among the PGMs.…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest in ILs is because of their unique properties, such as their low volatility, low flammability, and low melting point (Regel-rosocka and Wisniewski, 2011). It has recently been found that ILs themselves possess high extraction ability and selectivity for some metal ions, and their application as an extraction solvent (extractant) without dilution has been intensively studied (Yang et al, 2014;Svecova et al, 2016;Kubota et al, 2017). Undiluted phosphonium-based ILs have been applied to the recovery of various metals, such as precious and transition metals (Wellens et al, 2012;Vander Hoogerstraete et al, 2013;Firmansyah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Kozonoi & Ikeda, 2007). Regarding metals found in WEEE, these ILs were found to be efficient at extracting precious metals such as Au(III), Pt(IV) or Ir(IV) from acidic aqueous solutions containing large amounts of HCl (Génand-Pinaz et al, 2013;Papaiconomou et al, 2012Papaiconomou et al, & 2014Yang et al, 2014;Tong et al, 2015;Kubota et al, 2017 (Parmentier et al, 2015a) and was employed in a continuous selective metal extraction process for the recovery of cobalt from two mixed salt solutions (Co/Na, Ca/Co/K) (Parmentier et al, 2015b Figure 9. This process clearly shows the potential of ILs to recover metals from complex aqueous solutions using careful selection of the ILs and understanding their influence on the metal extracted complex (chloride vs. nitrate, etc).…”
Section: Cation Mediated Leachingmentioning
confidence: 99%